FAKTOR PENDUKUNG DAN FAKTOR PENGHAMBAT KEPUASAN HIDUP PEREMPUAN EMERGING ADULTHOOD YANG MENGALAMI OBESITAS - Kusuma, Yuviena Hendra; Prasetyo, Eli (Universitas Katolik Widya Mandala Surabaya, 2020)
Life satisfaction is one of the predictor to determine one's happiness. The more a person satisfied with life, the happier they are. Many factors can affect life satisfaction. These factors can be from within or from the outside of self. For emerging adult women that in a transition period of being adult can be related to life satisfaction. The changes that occurred during that period and also the obese condition bring out challenges for them. The cognitive process also changes. This study uses qualitative method and also using phenomenology approach. The informant of this study were three women with the ages range 18-25 years old who are obese. The informants are selected by using purposive sampling method and through snowball sampling. In addition, this study used inductive thematic analysis as the data analysis technique. The result shows that the factors that affect life satisfaction of emerging adult women who are obese consist internal factors and external factors. The internal factors are value of life, life experiences, self-control, the attitude when facing events in life, religiosity, and personality; whereas the external factors that affect life satisfaction of emerging adult women who are obese are relationship with others, social support, unpleasant experiences, and also the indictment from family.